Association of p53 Codon 72 Polymorphism with Risk of Hypopharyngeal Squamous Cell Carcinoma in Taiwan - Chih-Wen Twu; Rong-San Jiang; Chih-Hung Shu; Jin-Ching Lin (Journal of the Formosan Medical Association, 2006)
p53 polymorphism at codon 72 is a known risk marker for various malignancies, but it has not been studied in hypopharyngeal cancer. This study investigated the genotype distribution of p53 codon 72 polymorphism in hypopharyngeal cancer patients and non-cancer controls matched for age, gender, alcohol consumption and smoking habit. Methods: Genomic DNA was extracted from peripheral blood cells of 53 patients with hypopharyngeal cancer and 53 non-cancer controls. Codon 72 polymorphism of p53 was identified by polymerase chain reaction-restriction fragment length polymorphism. Results: Patients with hypopharyngeal cancer had higher frequencies of Pro/Pro (26.4% vs. 13.2%) and Pro/Arg (51.0% vs. 45.3%) but lower frequencies of Arg/Arg (22.6% vs. 45.1%) compared to controls. Compared to Arg/Arg genotypes, Pro/Pro genotypes had a relative risk of hypopharyngeal cancer of 3.667 (95% confidence interval, 1.16-11.56; p = 0.03). As a group, patients with Pro/Pro or Arg/Pro who were carriers of the Pro allele had a higher relative risk of hypopharyngeal cancer compared to Arg homozygous carriers (odds ratio, 2.415; 95% confidence interval, 1.04-5.64; p = 0.04). Conclusion: This study demonstrated that p53 codon 72 Pro homozygosity is associated with a higher risk of developing hypopharyngeal cancer.